Ultrasound of the Scrotum - Michael Jones (Association of American Medical Colleges, 2010)
Abstract Introduction This PowerPoint based e-learning module is a modification of the bedside scrotal ultrasonography session taught in the intermediate ultrasound course at our institution. It is also part of our developing ultrasound curriculum for fourth-year medical students and emergency medicine residents. Its purpose is to introduce students to techniques, instrumentation, and scanning protocols used in the evaluation of the scrotum. Methods Through a PowerPoint presentation and accompanying audio file, students are introduced to the common pathology related to acute scrotal complaints and the related sonographic findings. Pathology covered includes hydroceles, varicoceles, hernias, spermatoceles, trauma, tumors, epididymitis, orchitis, and torsion. At its conclusion, a number of actual patient cases are presented allowing the student an opportunity to implement skills learned in this module. This self-instructional program utilizes high quality images taken with the latest generation of ultrasound machines in order to provide the best possible examples of pathology and enhance the students ability to remember important sonographic features. A quiz is also included to assess student retention of key concepts. Results This resource has been presented at the Carilion Clinic's annual Ultrasound for the Critically Ill symposium. Physicians from all over the world with an interest in emergency, cardiac and critical care sonography were in attendance. The presentation was well received and rated overall "excellent" by the physicians attending the conference. The conference committee made the decision to increase the time allotment for this section on scrotal sonography the following year as 1 hour was not felt sufficient to get through all the material and the interest level was high. Discussion Through PowerPoint presentations and patient cases, this resource successfully introduces students to techniques, instrumentation, and scanning protocols used in the evaluation of the scrotum.